2016
DOI: 10.1016/j.jpor.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis caused by titanium screws and dental implants

Abstract: In general, allergic risk of titanium material is smaller than that of other metal materials. However, we suggest that pre-implant patients should be asked about a history of hypersensitivity reactions to metals, and patch testing should be recommended to patients who have experienced such reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 21 publications
0
69
0
5
Order By: Relevance
“…Although Ti is widely used in clinical practice because of its high biocompatibility, more and more literature in the recent past related to its sensitization and allergic response was reported . A case of contact dermatitis caused by the fractured end of the titanium nail fixation and the implant repair was reported . The investigators of Ti contact allergy patients found the allergy rate of 0.6% .…”
Section: Discussionmentioning
confidence: 99%
“…Although Ti is widely used in clinical practice because of its high biocompatibility, more and more literature in the recent past related to its sensitization and allergic response was reported . A case of contact dermatitis caused by the fractured end of the titanium nail fixation and the implant repair was reported . The investigators of Ti contact allergy patients found the allergy rate of 0.6% .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical reports have indicated that changing to porcelain or hybrid resin restorations and titanium dentures is the best way to treat patients with metal allergies 9,50) . Recently, allergic reactions to titanium implants have been reported and may gradually increase in the future [58][59][60] . Although implants, superstructures, and crown-bridges can be fabricated with zirconia as metal-free restorations, it would be difficult to use zirconia for RPD frameworks because zirconia bars and clasp arms are easily breakable.…”
Section: Biocompatibilitymentioning
confidence: 99%
“…Allergic reactions to gold in dental prostheses have been well documented since the 1980s [141]. More recent literature has also discussed allergic reactions in response to dental implants using nickel [142][143][144][145], titanium [141,146], and palladium [147].…”
Section: Dentalmentioning
confidence: 99%